Phenology of a dioecious population of Batrachospermum delicatulum (Batrachospermales, Rhodophyta) in a stream from southeastern Brazil - Necchi Jr., Orlando [UNESP]; Branco, Ciro C. Z. (My University, 1999)
The seasonal dynamics of a dioecious population of Batrachospermum delicatulum (Skuja) Necchi and Entwisle was evaluated biweekly during the growth period of the macroscopic gametophyte, from late autumn (May) to early spring (October) in a third-order stream from the northeast region of Sao Paulo State, southeastern Brazil (20°43'S, 49°13'W). The population fluctuated throughout the study period in terms of percentage cover, frequency and chlorophyll content. Percent cover and frequency showed a clear pattern with the lowest values at the initial and final stages of the growth period and the highest in July-August (winter). Gametophyte growth was associated with high illumination and low temperature, which agrees with most observations on Batrachospermales in stream environments. Relatively wide variations in reproductive characteristics were observed during the growth period, which were not correlated with percentage cover, frequency and chlorophyll content. The phenologic pattern observed in this population was characterized by a synchronic development of female/male plant ratio with the number of spermatangia per plant resulting in. (i) a higher proportion of fertilized (carposporophytic) plants associated with more male plants; (ii) higher fertilization rates during the periods with higher production of spermatangia per plant; and (iii) higher production of spermatangia per plant when the population had more male plants. These characteristics were largely associated with water temperature and ion content. In terms of reproductive success, the population studied can be regarded as highly efficient, considering the relatively low proportion of male to female plants and high fertilization rates. These data are consistent with a hypothesis to explain high fertilization rates in dioecious species in lotic habitats consisting of outcrossing among adjacent plants with intermingled male and female branches within an algal cluster. Efficient reproductive strategies have been reported in dioecious, monoecious and even mixed populations of B. delicatulum and can be interpreted as adaptations to successfully colonize streams with different characteristics.
Keywords: Batrachospermum; Dioecy; Phenology; Reproduction; Reproductive ecology; Reproductive strategy; Seasonality; dioecy; phenology; population dynamics; reproductive strategy; stream; Brazil; Batrachospermales; Batrachospermum delicatulum